Prevalence of Acute Dyspnea among College-going Regular Smokers in North India: A Survey Study - Abhishek Shrestha; Joydip Saha; Sunanda Bhowmik; Sandeep Pattnaik (Journal of the Scientific Society)
Contexts: Smoking remains the leading cause of preventable death globally, impacting health. Aims: This study aimed to investigate the prevalence of regular smokers experiencing acute dyspnea among college students in North India. Settings and Design: This study employed a cross-sectional design, recruiting 532 college students from a university in North India through a convenient sampling method. Materials and Methods: Participants self-reported their smoking habits and experiences of dyspnea through an online questionnaire hosted on Google Forms. The Modified Medical Research Council (MMRC) scale was used to assess the severity of dyspnea among regular smokers. Statistical Analysis: Data analysis was conducted using Microsoft Excel and SPSS software version 26. Results: Our findings revealed that over half (58%) of the participants reported smoking, with a third (34.21%) identified as regular smokers. Notably, 81.32% of regular smokers experienced breathlessness earlier than nonsmokers. The MMRC scale indicated that while most regular smokers fell under Grade 2 for dyspnea severity, Grades 1 and 3 were also present. Furthermore, the study established a clear link between the duration and frequency of smoking with the level of dyspnea experienced. Conclusion: This study identified a high prevalence of regular smoking among college students in North India. In addition, a strong correlation emerged between dyspnea and the students’ smoking habits, with both duration and frequency playing a role in the severity of breathlessness experienced.